Power, politics and maritime governance in the Indian Ocean - Schöttli, Jivanta (Routledge, 2015)
Power, politics and maritime governance in the Indian Ocean / Jivanta Schöttli -- The Indian Ocean Rim - Association for Regional Co-operation (IOR-ARC): the futile quest for regionalism? / Christian Wagner -- The Indian Ocean Region in India's strategic futures: looking out to 2030 / Krishnappa Venkatshamy -- The reluctant pretender: China's evolving presence in the Indian Ocean / Jonathan Holslag -- The French strategic vision of the Indian Ocean / Isabelle Saint-Mézard -- European (British and French) geostrategy in the Indo-Pacific / James Rogers -- The US Navy's Indo-Pacific challenge / Toshi Yoshihara -- Piracy and maritime governance in the Indian Ocean / Peter Lehr.
The chapters in this book were originally published in the Journal of the Indian Ocean Region, volume 9, no. 1 (June 2013) -- Page vii
The compilation of papers for this special issue arose out of a two-day, international symposium that took place in Heidelberg, Germany during the summer of 2012 -- Page 1
Includes bibliographical references and index
Keywords: Indian Ocean Region -- Politics and government -- Congresses; Indian Ocean Region -- Strategic aspects -- Congresses